Unravelling decomposition products of phosphine under high pressure. (25th January 2018) - Liu, Mingkun; Huang, Xiaoli; Wang, Xin; Huang, Yanping; Li, Fangfei; Wu, Gang; Li, Xin; Liang, Yongfu; Zhou, Di; Lu, Mengya; Liu, Bingbing; Cui, Tian
Abstract: Recently, the superconductivity in phosphine (PH3 ) has been discovered with the superconducting transition temperature T c up to 203 GPa by using high pressure resistance measurements. However, the structural information of PH3 under high pressure remains elusive. Motivated by this, in this work, the behavior of PH3 under high pressure has been investigated by Raman spectroscopy at 298 K. The Raman spectra varied with pressure increasing, accompanying with the change of the sample color, which first became yellow, then red, and finally opaque. In the pressure range of 8.53–18.36 GPa, the decomposition of PH3 was observed, and the main decomposition products were P2 H4 and element hydrogen (H2 ). Upon compression to higher pressure, the Raman signal of hydrogen vibration was observed to become stronger, indicating that PH3 or P2 H4 further decomposed into element phosphorus and hydrogen. The original PH3 did not form again upon decomposition to ambient pressure. P2 H4 and other decomposition products of compressed phosphine were considered as main products of the high temperature superconducting phase reported in experiment. Abstract : The behavior of PH3 under high pressure has been investigated by Raman spectroscopy at 298 K. PH3 will decompose under the effect of pressure. By applying pressure, two reactions may occur: PH3 decomposes into P2 H4 and hydrogen, PH3 or P2 H4 decomposes into hydrogen and element phosphorus.